THE EFFECT OF LEARNING MOTIVATION AND SELF-EFFICACY ON ENGLISH LEARNING ACHIEVEMENT - Viviana Lisma Lestari; Suwarsito Suwarsito (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2020)
This study aims to analyze the effect of learning motivation and self-efficacy on English learning achievement. It was motivated by the efforts of Al-Lughah Bogor to continue to strive to follow the development of the world of education in order to improve the quality of services, human resources and the quality of its graduates. The research object used was Al-Lughah Bogor students representing all levels of education as many as 56 students. To analyze the research data, SPSS Version 20 was used. The results showed that (1) Learning Motivation had a positive and significant effect on Student Achievement in Al-Lughah Bogor Students, (2) Self Efficacy had no significant effect on Student Achievement in Al-Lughah Bogor Students, (3)) Learning motivation and self-efficacy together have a significant effect on the learning achievement of Al-Lughah students in Bogor